On Key Evolution over Wireless Channels - Zhihong Liu; Yong Zeng; Pingjuan Zhang; Qiping Huang (International Journal of Distributed Sensor Networks)
Noise is a powerful resource for the implementation of cryptographic primitives, especially in wireless networks. In general, a key agreement protocol is tailored to the channels and relies on the assumption that knowledge on the eavesdropper's channel is available. This is not practical. In this paper, we focus on the problem of developing key agreement schemes for secure communication across wireless channels and propose a key evolution scheme to alleviate the assumption. Keys evolve continuously based on the transmitted messages over the noisy wireless channel. Even if the eavesdropper's channel is superior to the legitimate receiver, the legitimate parties can establish secret keys. To further confuse the eavesdropper, we present a strategy for legitimate parties to send artificial noise if the eavesdropper cannot distinguish the sources of messages. Finally, we propose a k -resistant encryption scheme that can use different keys to encrypt and decrypt messages if there are no more than k bits which differ between the encryption and decryption keys.